2013
DOI: 10.2172/1064546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Ventilation Systems for Existing Homes

Abstract: iv [This page left blank]v

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another advantage of installing a ventilation system is that any future tightening of the envelope can be more easily accommodated. Recent studies have compared the cost and performance of various whole-house ventilation strategies in retrofitted homes (Aldrich & Arena, 2013;LBNL, 2012 …”
Section: Ventilationmentioning
confidence: 99%
“…Another advantage of installing a ventilation system is that any future tightening of the envelope can be more easily accommodated. Recent studies have compared the cost and performance of various whole-house ventilation strategies in retrofitted homes (Aldrich & Arena, 2013;LBNL, 2012 …”
Section: Ventilationmentioning
confidence: 99%
“…In addition to maintaining a suitable temperature, if used efficiently, ventilation can play a key role in controlling the exposure of workers to ENPs. There are a broad range of techniques that can be used for this purpose, from point-source ventilation to fullroom ventilation [66]. Hämeri et al [4] showed that nanosized particles were effectively cleaned and exhausted from the breathing zone as a result of using the "displacement flow" principle.…”
Section: Exposure Control In Nanotechnology Workplacesmentioning
confidence: 99%
“…However, it has been reported that in reality few local exhaust fans are working properly [1]. For example, in a field study conducted by [13], measurements on 43 bathroom exhaust fans showed that actual airflow rates were between 8% and 105% of the rated values with an average of 67%, which indicates a significantly reduced airflow rate for units in the field.…”
Section: Introductionmentioning
confidence: 99%